Effect of winter canola cultivar on seed yield, oil, and protein content. Issue 1 (9th March 2022) - McGeary, Kyle D; de Koff, Jason; Pokharel, Bharat; Link, Richard; Saini, Priya; Gill, Taqdeer
Abstract: Winter canola ( Brassica napus L.) production has increased in the United States over the past several decades; however, there is little research in the southeastern United States on its agronomic production and growth characteristics under different nitrogen (N) fertilizer rates. The objectives of this study were to determine the effects of N rates on winter mortality, yield, oil and protein content, and seedpod shatter resistance across cultivars. Canola was grown in a randomized split complete block design with four replicates under five different N rates (0, 56, 112, 168, and 224 kg N ha −1 ) with four different cultivars (Hekip, Inspiration, and Edimax CL or Phoenix CL). Seed yield was very low for the 2017–2018 season, likely due to extreme cold conditions in winter and/or frost at flowering. There was high winter mortality during this period, but Edimax CL had significantly lower mortality (79.7%) than Inspiration (85.7%) and Hekip (83.9%). In the following year, more mild temperatures led to low mortality and greater yields, where rates of 112, 168, and 224 kg N ha −1 had the greatest yields (1, 612–1, 857 kg ha −1 ) with no significant differences according to cultivar. In 2018, shatter resistance was greatest for the rates of 112, 168, and 224 kg N ha −1 and was positively related to N rate. Across both years, Inspiration had greater shatter resistance. In 2019, the lowest N rate (0 kg N ha −1 ) and Phoenix CL had significantly greater oil contents (48.4 and 47.3%, respectively), whereas the highest N rate (224 kg N ha −1 ) with no particular cultivar had a significantly greater protein content (21.0%). Core Ideas: Cultivars like Edimax CL may help reduce winter mortality under extreme cold conditions. Higher nitrogen rates had significantly greater resistance to seedpod shatter. A nitrogen rate of 112 kg ha −1 and the Inspiration cultivar are recommended.